PEMANFAATAN SURVEI GEOLISTRIK DAN GEOTEKNIK UNTUK IDENTIFIKASI STRUKTUR BAWAH PERMUKAAN RENCANA JALAN LINGKAR POLITEKNIK PERTANIAN NEGERI SAMARINDA - SM, A. Arifin Itsnani; Tahrir, Muhammad; Ridwan, Ridwan; Akshar, Muhammad; Barus, Mika Debora Br; Sutadji, Ahmad Aris Mundir (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
Soil conditions with weak zone points can cause damage to road structures such asland subsidence. Geoelectric surveys can identify subsurface structures based onvariations in rock resistivity. Road infrastructure crash due to weak zones of soilbearing capacity can be identified by geoelectric surveys and geotechnical tests assupporting analysis. Based on the master plan of Politani Samarinda 2025-2029 inthe southern area, a ring road of ± 1.5 km will be built, so geoelectric andgeotechnical support data are first needed as a basis for road planning. The mainobjective of this study is to mapping subsurface structure and identify the stability ofthe strong and weak zones of the soil in the planned area of the ring roadconstruction. The geoelectric resistivity survey uses the Wenner Schlumbergerconfiguration with 2 longitudinal tracks of ± 100 m per track with a spacing (a) of 5m which can identify the distribution of subsurface resistivity values laterallymapping.The resistivity value obtained from 2D geoelectric inversion is the lowestvalue of 2.62 ohm.m which is suspected as clay, medium 78.5 ohm.m which issuspected as sand, and the highest 7716 ohm.m which is suspected as sandstoneand used as a reference in the strong zone of the road building foundation.Furthermore, the USCS classification geotechnical test at 2 track points resulted insand (SM) and silt clay (MH) soil types based on mechanical laboratory tests. Theresults of the identification of geoelectric surveys and geotechnical tests have asignificant correlation with road construction that has a potential strong zonebearing capacity because the top soil is in the form of silt, clay, sand which isunderneath in the form of sandstone which is strong enough to withstand the load ofroad construction.